Epidemiological aspects of tuberculosis in HIV infected children - E. B. Vasilieva; M. E. Lozovskaya; L. V. Klochkova; Yu. A. Yarovaya; O. M. Noskova (Туберкулез и болезни лёгких)
The objective: to assess the methods and time of detection of tuberculosis and HIV infection in children with the co-infection, epidemiological risk factors to develop tuberculosis and effectiveness of preventive measures.Subjects and methods. 75 children in the age from 0 to 14 years old were enrolled in the study. The TB/HIV Group included 25 children with TB/HIV co-infection. The TB Group included 50 HIV negative children with tuberculosis, they made a comparison group.Results: out of 25 children with TB/HIV, only 18 (72%) were aware of perinatal exposure to HIV. HIV infection was confirmed in 11/25 (44%) children during the first months of life, in the remaining 14/25 (56%) it was confirmed later, the latest at 13 years old. In 4 children, HIV infection was detected during examination for tuberculosis. In the TB/HIV Group, in 14/25 (56%) children were exposed to tuberculosis in their families as well as 35/50 (70%) in the TB Group. The positive result of a sputum test of the index case was registered in 7/14 (50%) children of the TB/HIV Group and 19/35 (54.2%) children of the TB Group. Of 25 children of the TB/HIV Group, 17 children (68%) were vaccinated with BCG, and in 9 of them the vaccination was not done properly.